PELATIHAN PRAKTIS: PEMBUATAN HAND SANITIZER ALAMI BERBASIS BAHAN SEDERHANA DI SD NEGERI 032 BALIKPAPAN UTARA - Eka Megawati; Meita Rezki Vegatama; Debora Ariyani; I Ketut Warsa; Junety Monde; Yuniarti; Amirul Mukminin; Adnan Mufti Naufal; Elya Rahmadany; Gabriel Pamasi; Nixie Naiya Althea; Muhammat Rahmat Ilham; Muhammad Aditya Arisma; Cantika; Rahmadani (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity aims to increase the understanding and awareness of elementary school students regarding the importance of hand hygiene through practical training in making natural hand sanitizers based on simple ingredients. The activity was carried out at SD Negeri 032 Balikpapan Utara by lecturers and students of the Oil and Gas Processing Engineering Study Program as a form of implementing the Tri Dharma of Higher Education. The implementation method included the preparation stage, interactive material delivery, demonstration of hand sanitizer making, direct practice by participants, and activity evaluation. A total of ± 91 students participated in the activity enthusiastically and were actively involved in the entire training series. The results of the activity showed that participants were able to understand the basic concepts of hand hygiene and practice making natural hand sanitizers independently with the guidance of the implementation team. The resulting hand sanitizer product has characteristics suitable for daily use and is safe to use. In addition to providing educational benefits for students, this activity also improves students' communication skills, cooperation, and social awareness. Overall, this training is effective as a medium for health education and applied science for elementary school students.